(untitled) (Prithvi Academic Journal, 2026)
Invasive and alien plant species are increasingly reported to affect agricultural landscapes and ecosystems in Nepal. Their effects on crop production and native biodiversity have rarely been investigated. Different phytochemicals in the invasive plants enter the soil and are transported to the farmlands and cause negative impacts on the germination and development of staple plants. This research examined the allelopathic impacts of one of the most widespread invasive plants, Ageratum houstonianum on the germination and early growth of Eleusine coracana and Raphanus sativus. The methanolic leaf extract of A. houstonianum was found to contain several classes of secondary metabolites including alkaloids, flavonoids, phenolics, and reducing sugars on phytochemical screening. The leaf extract exhibited no significant antibacterial activity against Staphylococcus aureus, Escherichia coli and Pseudomonas aruginosa. Treatment with 10% extract reduced plumule growth by 22.79% and radicle growth by 27.86% in R. sativus, and germination rates were significantly decreased in both crop species. Although the extract inhibited seedling growth in R. sativus, E. coracana showed a significant stimulatory response, with growth increasing by 190.48% at the 10% extract concentration. The results of this study will support the management of invasive alien species for the sustainable crop production and preservation of biodiversity.